Investigating the Relationship of Employee Empowerment and Sustainable Manufacturing Performance - Yusoff, Rosman Bin Md; Imran, Amina; Qureshi, Muhammad Imran; Kazi, Abdul Ghafoor (International Review of Management and Marketing, 2016)
Literature identified employee empowerment under the socio-technical context can help to enhance sustainable manufacturing performance (SMP). However, few studies have attempted to empirically test the relationship between the employee empowerment and SMP. The current study focused on the investigation of the relationship between employee empowerment and SMP. The study used quantitative research design to address the problem. The study used random sample of 100 employees from large manufacturers in Malaysia to collect data on a 5 point- likert scale questionnaire adopted from the literature. Further, this data statistically tested using SmartPLS (Structural Equation Modeling) to empirical investigations of the relationships between employee empowerment and SMP. Results indicated that employee empowerment has a positive relationship with social, environmental and economic performance of the manufacturers in Malaysia. A result of the study suggests to the policy makers to enhance level of employee empowerment in order to improve sustainable manufacturing performance. Keywords: employee empowerment, sustainable manufacturing performance, Structural Equation Modeling JEL Classifications: J5, L6